LIMITATIONS OF REVISION THE LEGISLATIONS IN THE PROCESS OF FORMULATING THE LEGISLATIONS IN INDONESIA - Eka NAM Sihombing; Dani Sintara; Cynthia Hadita (NOMOI Law Review, 2022)
The absence of a limit on the number of times a law is allowed to change is a problem in the law-making process. Considering that there is still a mechanism in the form of an option to revoke a law which can be replaced with a new one if more than half of its substance has been changed. However, there is a law that has made a third amendment and even a fourth amendment. This needs to be studied in the perspective of the formation of laws and regulations. The research method used is normative juridical. The results of the study indicate that there is no benchmark/standardization of how much maximum a law can be amended and if more substances have been changed, it should be revoked and replaced with a new one instead of repeated changes, so it needs to be regulated in Law No. 12 of 2011 concerning the Establishment of Legislation.